A phase III study of triple therapy with budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler 320/18/9.6 μg and 160/18/9.6 μg using co-suspension delivery technology in moderate-to-very severe COPD: The ETHOS study protocol. (October 2019) - Rabe, Klaus F.; Martinez, Fernando J.; Ferguson, Gary T.; Wang, Chen; Singh, Dave; Wedzicha, Jadwiga A.; Trivedi, Roopa; St Rose, Earl; Ballal, Shaila; McLaren, Julie; Darken, Patrick; Reisner, Colin; et al.
Abstract: Background: Single inhaler triple therapies providing an inhaled corticosteroid, a long-acting muscarinic antagonist, and a long-acting β 2 -agonist (ICS/LAMA/LABAs) are an emerging treatment option for chronic obstructive pulmonary disease (COPD). Nevertheless, questions remain regarding the optimal patient population for triple therapy as well as the benefit:risk ratio of ICS treatment. Methods: ETHOS is an ongoing, randomized, double-blind, multicenter, parallel-group, 52-week study in symptomatic patients with moderate-to-very severe COPD and a history of exacerbation(s) in the previous year. Two doses of single inhaler triple therapy with budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler (BGF MDI 320/18/9.6 μg and 160/18/9.6 μg) will be compared to glycopyrrolate/formoterol fumarate (GFF) MDI 18/9.6 μg and budesonide/formoterol fumarate (BFF) MDI 320/9.6 μg, all formulated using co-suspension delivery technology. Outcomes include the rate of moderate/severe (primary endpoint) and severe COPD exacerbations, symptoms, quality of life, and all-cause mortality. Sub-studies will assess lung function and cardiovascular safety. Study population: From June 2015–July 2018, 16, 044 patients were screened and 8572 were randomized. Preliminary baseline demographics show that 55.9% of patients had experienced ≥2 moderate/severe exacerbations in the previous year, 79.1% were receiving an ICS-containing treatment at study entry, and 59.9% had blood eosinophil counts ≥150 cells/mm 3 . Conclusions: ETHOS will provide data on exacerbations, patient-reported outcomes, mortality, and safety in 8572 patients with moderate-to-very severe COPD receiving triple and dual fixed-dose combinations. For the first time, ICS/LAMA/LABA triple therapy with two different doses of ICS will be compared to dual ICS/LABA and LAMA/LABA therapies. Clinical trial registration number: NCT02465567. Highlights: Budesonide/glycopyrrolate/formoterol metered dose inhaler is a triple therapy for COPD. ETHOS will investigate exacerbations, patient-related outcomes, safety & mortality. > 8500 patients with moderate-to-very severe COPD. Triple therapy with 2 different ICS doses will be compared to ICS/LABA and LAMA/LABA. Findings are expected to help refine current treatment recommendations.